البلاء والابتلاء في ميزان القرآن الكريم الكوارث الطبيعية في إندونيسيا أنموذجا - عبد الرحمن، أشرف جلال الدين (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2021)
This study analyzed the meanings of al-bala' and al ibtila' in the Quranic perspective by examining verses related to them from the point of view of mufassir. This study adopted two main approaches, inductive and analytic. The former was used to collect data from various references, and the latter was used to analyze verses related to al-bala' and al ibtila'. The results of the study showed that the original meaning of al-bala' and al ibtila' is test. The meanings of these words are not necessarily negative. Instead, al bala' and al ibtila' are Allah's wisdoms with the objective of testing man of their faith. al bala' and al ibtila', however, do not mean Allah's blessing either. In actuality, the meanings refer to Allah's mercy by sending reminders to His creations to remember Him as stipulated in man's Covenant with the Creator. Furthermore, Allah's reminders in the form of natural disasters in Indonesia and in other places are due to the degradation of aqidah and morality, as well as the destruction of the environment. These reminders from Allah are found in the Al Quran which gives instructions in facing hardships and tests in dealing with disasters and calamities, natural or man-made. The Al Quran urges man to do zikir, seek forgiveness, pray, remain patient, and to calmly accept Allah's will, as well as to continue to do good deeds.